Embedding Crowdfunding Structure in Islamic Venture Capital for SMEs Development - Athief, Fauzul Hanif Noor (Economica: Jurnal Ekonomi Islam, 2019)
SMEs that play significant role in Indonesia economy still suffer from financial constraint. Even though government provides big support to open finance access for SMEs, there are still more than half are not supported by sufficient access of financing. This paper investigates the possible financing methods that can be used by SMEs by examining its positive and negative aspects along with the shariah view on it. Since there are limitations that have to be removed, we propose new scheme of financing suits best for Indonesia SMEs based on the venture capital design by embedding crowdfunding structure and the Islamic element in it. This paper also proposes new possible exit strategy for the scheme in order to benefit all parties involved.UKM memiliki peran penting dalam perekonomian Indonesia yang masih mengalami kendala keuangan. Meskipun pemerintah memberikan dukungan besar untuk membuka akses keuangan untuk UKM, masih ada lebih dari setengah yang tidak didukung oleh akses pembiayaan yang memadai. Kajian ini meneliti kemungkinan metode pembiayaan yang dapat digunakan oleh UKM dengan memeriksa aspek positif dan negatifnya disertai dengan pandangan syariah atas permasalahan ini. Karena ada keterbatasan yang harus dihilangkan pada model-model pembiayaan, maka kami mengusulkan skema baru pembiayaan yang terbaik untuk UKM Indonesia berdasarkan desain modal ventura dengan menanamkan struktur crowdfunding dan elemen Islami di dalamnya. Penelitian ini juga mengusulkan kemungkinan strategi keluar baru untuk skema tersebut agar bermanfaat bagi semua pihak yang terlibat.